Identification of Vermamoeba vermiformis and Tetramitus sp. Isolated from the Gills of Oreochromis sp. (Red Hybrid Tilapia) - Wan NorNadhirah Wan Noor Azmi; Fatimah Hashim; Zarizal Suhaili; Suzana Misbah; Nor Hafizah Zakaria (Bogor Agricultural University, Indonesia, 2023)
This study is the first report of an infestation of amoeba in the gills of asymptomatic Oreochromis sp. from the Manir River, Terengganu, Malaysia. The results confirmed the presence of two species of amoeba, Vermamoeba vermiformis and Tetratmitus sp., based on the 18 ribosomal RNA gene sequences with 99% sequence similarity. Morphological observations using light and scanning electron microscopy supported the findings, demonstrating both amoeba species' specific features and locomotions. In the trophozoite stage, the mean size of V. vermiformis in the locomotive form was between 25.55 µm in length and 4.17 µm in width. The mean size of Tetramitus sp. was 20.96 µm in length and 8.66 µm in width. The diameter of the cyst for V. vermiformis was 4.67 µm and Tetramitus sp. was 3.37 µm. V. vermiformis was characterized by cylindrical trophozoites and single monopodial morphology. Tetramitus sp. showed a limax-type and various cell shapes. Infestation of the amoeba was also confirmed by histopathological observation in the lamella region with distinct amoeba characteristics compared to the lamellae's epithelial tissue. These findings revealed the presence of V. vermiformis and Tetramitus sp. infestation in the gills of Oreochromis sp. and its potential pathogenic activity, whilst the symbiosis interaction in Oreochromis sp. is still unidentified.